Linguagem e decolonialidade: análise panorâmica de produções acadêmicas no Brasil - Silva, Giselle Ribeiro da (2021)
This research aimed to elaborate a panoramic analysis of studies produced in Brazil hav-ing as central theme “language and decoloniality. The interest arose from the observation of the expansion of the uses of these terms in academic works and events, gaining wide prominence in universities and in society. This research thus focuses on the essential con-cepts underlying decolonial thinking. In this sense, we searched for more prominent the-ories, from the advent to the present moment of conceptual and critical amplification of the thoughts elaborated by the collective called Latin American Modernity/Coloniality Research Program, which investigate modernity/coloniality in the experiences that arise mainly in and from America Latin. The theoretical support for the construction of this work and the analysis of the empirical material comes from the contributions of authors who constitute this collective, but also from others considered relevant as a critical view and/or expansion of the Program theoretical elaborations. The empirical material ana-lyzed is composed of articles that correlate language and decoloniality in order to observe the meanings and contributions to language studies in Brazil. Therefore, the methodology is centered on bibliographical research, of a qualitative character, outlined as meta-re-search. In this sense, the research is configured by the meanings and themes that are pre-sent in the various texts found. These works significantly enrich the contemporary pano-rama, problematizing contexts, relationships and existences, still centered on an Eurocen-tered modern/colonial rationality.